2023
DOI: 10.1002/ptr.7703
|View full text |Cite
|
Sign up to set email alerts
|

Shenlian extract decreases mitochondrial autophagy to regulate mitochondrial function in microvascular to alleviate coronary artery no‐reflow

Abstract: Shenlian (SL) extract has been proven to be effective in the prevention and treatment of atherosclerosis and myocardial ischemia. However, the function and molecular mechanisms of SL on coronary artery no‐reflow have not been fully elucidated. This study was designed to investigate the contribution of SL extract in repressing excessive mitochondrial autophagy to protect the mitochondrial function and prevent coronary artery no‐reflow. The improvement of SL on coronary artery no‐reflow was observed in vivo expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have suggested that excessive mitophagy might result in mitochondrial damage (30)(31)(32). To evaluate whether iGF-1 protect mitochondrial damage based on mitophagy, the present study initially measured the engulfing mitochondria using co-localization of autophagosomes and mitochondria.…”
Section: Igf-1 Diminishes Pa-induced Mitophagy In Macrophagesmentioning
confidence: 99%
“…Previous studies have suggested that excessive mitophagy might result in mitochondrial damage (30)(31)(32). To evaluate whether iGF-1 protect mitochondrial damage based on mitophagy, the present study initially measured the engulfing mitochondria using co-localization of autophagosomes and mitochondria.…”
Section: Igf-1 Diminishes Pa-induced Mitophagy In Macrophagesmentioning
confidence: 99%